EFFECTS OF BACTERIAL ENDOTOXIN ON METABOLISM : I. CARBOHYDRATE DEPLETION AND THE PROTECTIVE ROLE OF CORTISONE - Berry, L. Joe (The Rockefeller University Press, 1959)
Mice of different strains were protected against the lethal effect of bacterial endotoxin by concurrent injections of cortisone. Either inadequate amounts of cortisone or excessive quantities of endotoxin voided the protection. Analyses of blood sugar, liver glycogen, muscle glycogen, and total body carbohydrate in the skinned eviscerated carcass were carried out on different strains of mice given endotoxin and/or cortisone. Poisoned animals were virtually depleted of all carbohydrate while mice given cortisone alone had concentrations of carbohydrate from three to four times that of normal mice. Mice given a lethal amount of endotoxin and a protective dose of cortisone had two to three times as much carbohydrate as animals injected with the same amount of endotoxin alone but significantly less than that found in normal mice. Dibenzyline failed to alter the lethal effect of endotoxin and to reduce the carbohydrate loss that accompanied endotoxin administration. Endotoxin, at the dosage level employed, lowered the temperature of mice 2°–3°C. during the first hour or two postinjection and the temperature remained essentially unaltered during the next 4 to 5 hours. Loss in body carbohydrate in endotoxin-poisoned mice cannot be explained, therefore, as the result of an elevated metabolic rate accompanying hyperthermia. Endotoxin prevented the conversion of injected glucose into liver glycogen but not into muscle glycogen. Mouse liver mitochondria, in the presence of endotoxin, released from ATP approximately the same amount of inorganic phosphate as that released in the presence of dinitrophenol.